Comprehensive discovery of novel structured noncoding RNAs in 26 bacterial genomes. Issue 12 (2nd December 2021) - Brewer, Kenneth I.; Greenlee, Etienne B.; Higgs, Gadareth; Yu, Diane; Mirihana Arachchilage, Gayan; Chen, Xi; King, Nicholas; White, Neil; Breaker, Ronald R.
ABSTRACT: Comparative sequence analysis methods are highly effective for uncovering novel classes of structured noncoding RNAs (ncRNAs) from bacterial genomic DNA sequence datasets. Previously, we developed a computational pipeline to more comprehensively identify structured ncRNA representatives from individual bacterial genomes. This search process exploits the fact that genomic regions serving as templates for the transcription of structured RNAs tend to be present in longer than average noncoding 'intergenic regions' (IGRs) that are enriched in G and C nucleotides compared to the remainder of the genome. In the present study, we apply this computational pipeline to identify structured ncRNA candidates from 26 diverse bacterial species. Numerous novel structured ncRNA motifs were discovered, including several riboswitch candidates, one whose ligand has been identified and others that have yet to be experimentally validated. Our findings support recent predictions that hundreds of novel ribo-switch classes and other ncRNAs remain undiscovered among the limited number of bacterial species whose genomes have been completely sequenced.